PENGEMBANGAN MEDIA TEKA-TEKI SILANG DIGITAL BERBASIS ECLIPSE CROSSWORD PADA MATERI IPAS PERUBAHAN WUJUD ZAT - Elva Nurul Laila; Muhammad Nuruddin, Nuruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the need for learning media innovation that is adaptive to technological developments to overcome students' difficulties in understanding abstract concepts in science subjects. This research was conducted at Jatirejo State Elementary School, Jombang Regency with 4th grade students as subjects. The selection of location and subjects was based on the needs of elementary school students who often experience difficulties in understanding abstract concepts, with the aim of developing digital crossword puzzle learning media based on Eclipse Crossword on the topic of changes in the state of objects, and evaluating the level of feasibility and attractiveness as a means of independent learning. The method used is Research and Development (R&D) by applying the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data collection instruments consisted of validation sheets for material experts and media experts, as well as student response questionnaires to measure aspects of readability and attractiveness. The results showed that the developed digital crossword puzzle media was categorized as "Very Feasible" based on the assessment of material experts with a score of 86.25% and media experts at 91%. During the implementation phase, the field trial with students resulted in a "Very Interesting" rating with an average score of 80 and a positive response rate of 91%. These findings demonstrate that integrating digital educational games into the instructional process can create a more dynamic learning environment. In conclusion, the Eclipse Crossword-based digital crossword puzzle is effective, valid, and practical as an interactive learning tool to increase student engagement and motivation in learning the concept of changes in the state of matter.